The Relationship Between Mother's Knowledge Level and Behavior Use of Antibiotics in Children Aged 2-5 Years in Children's Polyclinic of Sitiung I Community Health Center, Sitiung Regency Dharmasraya - Ita Dwiani; Sri Fawziyah; Yulia Kenatia (Jurnal Kesehatan, 2025)
Introduction: The use of antibiotics in children aged 2–5 years is an important public health issue because at this age the immune system is still developing, so children are more susceptible to bacterial infections. This study aims to analyze the relationship between maternal knowledge levels and antibiotic use behavior in children aged 2–5 years at the Children's Polyclinic of Sitiung 1 Community Health Center, Dharmasraya Regency in 2025. Methods: This study used a descriptive correlational design with a cross-sectional approach. The population in this study were all mothers with children aged 2–5 years who visited the Children's Polyclinic of Sitiung 1 Community Health Center. Sampling was carried out using a purposive sampling technique of 80 respondents. The research instrument used a structured questionnaire. Bivariate analysis was carried out using the Spearman Correlation test with a significance level of 5% (p <0.05). Results: The analysis showed a correlation coefficient (r) of 0.062 with a p value = 0.584 (p <0.05). Conclusion: there is no positive relationship with very low strength between maternal knowledge levels and antibiotic use behavior in children. This study recommends that healthcare workers improve education regarding the appropriate use of antibiotics, strengthen communication with mothers, and encourage active participation in outreach programs. These efforts are expected to reduce the risk of antibiotic resistance and improve child health.